Phenylethanoid Glycosides form Verbascum sinaiticum - Elgindi, M.R.; Mabry, T.J. (Asian Journal of Chemistry, 2010)
Two known phenylethanoid glycosides, 2'-acetylacteoside and arenarioside, and two new ones, β-(3,4-dihydroxyphenyl)-ethyl-O- α-L-rhamnopyranosyl (1→3)-β-D[β-D-xylopyranosyl (1→6)]- (4-O-isoferulyl)-gluco- pyranoside (3) and β-(3-hydrosy-4-methoxy phenyl)-ethyl-O-α-L-rhamnopyranosyl (1→3)-β-D[β-D-glucopyranosyl (1→6)]-4-O-isoferulyl)-glucopyranoside (4), were isolated and identified from aerial parts of Vebascum sinaiticum. The structures of all compounds were established by chromatographic and spectroscopic methods. This is the first report of phenylethanoid glycosides from Verbascum sinaiticum.